The neural substrates of in-group bias a functional magnetic resonance imaging investigation - Van Bavel ,Jay J.; Packer, Dominic J. (2008)
Classic minimal-group studies found that people arbitrarily assigned to a novel group quickly display a range of perceptual, affective, and behavioral in-group biases. We randomly assigned participants to a mixed-race team and used functional magnetic resonance imaging to identify brain regions involved in processing novel in-group and out-group members independently of preexisting attitudes, stereotypes, or familiarity. Whereas previous research on intergroup perception found amygdala activity?typically interpreted as negativity?in response to stigmatized social groups, we found greater activity in the amygdala, fusiform gyri, orbitofrontal cortex, and dorsal striatum when participants viewed novel in-group faces than when they viewed novel out-group faces. Moreover, activity in orbitofrontal cortex mediated the in-group bias in self-reported liking for the faces. These in-group biases in neural activity were not moderated by race or by whether participants explicitly attended to team membership or race, a finding suggesting that they may occur automatically. This study helps clarify the role of neural substrates involved in perceptual and affective in-group biases.
Keywords: In-group bias